The Influence of Digital Marketing and Product Quality on Purchasing Decisions for Skincare Skintific Products for members of GenBi Lampung Province - Ali, Sopian; Habiburachman (Banking & Management Review, 2025)
Introduction/Main Objective: This paper discusses the influence of digital marketing and product quality on purchasing decisions for Skintific skincare products among Gen-BI members in Lampung Province. In today’s digital era, effective marketing strategies are essential to attract consumers, especially the younger generation who are connected to technology. Background Problems: This study examines how digital marketing and product quality influence purchasing decisions for skincare, posing the research question: "Do digital marketing and product quality influence purchasing decisions for Skintific products among Gen-BI members in Lampung Province?" Novelty: The uniqueness of this study lies in its specific analysis of the impact of these two factors within the context of the Gen-BI community, which has not been extensively researched before, thus filling a gap in the existing literature regarding the relationship between digital marketing strategies and consumer decisions in the skincare sector. Research Method: The research method used is quantitative with a descriptive approach. Data were collected from 83 Gen-BI members using purposive sampling and analyzed through multiple linear regression with SPSS Statistics 25, with the sample size determined using the Slovin formula at a margin of error of 10%. Findings/Results: The results indicate that digital marketing has a positive influence on purchasing decisions, while product quality also has a significant impact, underscoring the importance of both factors in shaping consumer behavior when choosing skincare products. Conclusion: The study concludes that digital marketing and product quality simultaneously have a significant influence on purchasing decisions for Skintific products among Gen-BI members.